Dialect: Traditions in Culture and Innovations in Analysis - Kretzschmar, Jr., William A. (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1992)
Every generation believes that the dialects of its day are fast disappearing, but academic analysis cannot validate the existence of dialects that the general public perceives to exist. I propose to discuss why that is the case, and suggest how a new generation of analyses might account for popular perceptions within a framework of change and shifting boundaries.